2006
DOI: 10.1063/1.2214299
|View full text |Cite
|
Sign up to set email alerts
|

Er coordination in Y2O3 thin films studied by extended x-ray absorption fine structure

Abstract: Extended x-ray absorption fine structure (EXAFS) spectroscopy was employed to study the Er coordination in polycrystalline Y2O3 thin films, which was found to dictate their photoluminescence (PL) properties. Incorporation of Er with concentrations varying from 6to14at.% was achieved by radical-enhanced atomic layer deposition at 350°C. In all samples, Er was found to be in the optically active trivalent state, confirmed by their x-ray absorption near-edge spectroscopy spectra. Modeling of the EXAFS data reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…A classic example is the ALD of metal oxides from b-diketonate precursors, such as those with acac (acetylacetonate), [97][98][99][100] hfac (1,1,1,5,5,5-hexafluoroacetylacetonate), 101,161,162 and thd (2,2,6,6,-tetramethyl-3,5-heptanedionato) 102,104,[275][276][277][278][279] ligands. Such precursors require more reactive co-reactants as they show no or low reactivity with H 2 O (in essence, they do not readily undergo hydrolysis reactions).…”
Section: Increased Choice Of Precursors and Materialsmentioning
confidence: 99%
“…A classic example is the ALD of metal oxides from b-diketonate precursors, such as those with acac (acetylacetonate), [97][98][99][100] hfac (1,1,1,5,5,5-hexafluoroacetylacetonate), 101,161,162 and thd (2,2,6,6,-tetramethyl-3,5-heptanedionato) 102,104,[275][276][277][278][279] ligands. Such precursors require more reactive co-reactants as they show no or low reactivity with H 2 O (in essence, they do not readily undergo hydrolysis reactions).…”
Section: Increased Choice Of Precursors and Materialsmentioning
confidence: 99%
“…1,8 First, the selection of a favorable host material is critical. 1,9 In this work, Y 2 O 3 is selected as a favorable host material for erbium ion substitution due to the following reasons: ͑1͒ Er 2 O 3 and Y 2 O 3 have identical cubic bixbyite crystal structures with very similar lattice constants and Y 3+ and Er 3+ ions have nearly the same ionic radii; ͑2͒ Y 2 O 3 is a refractory oxide that has a high melting point ͑ϳ2400°C͒, a very high thermal conductivity ͑ Y 2 O 3 =27 W/ mK͒, chemical stability, optical isotropicity with a refractive index of 1.91, and low phonon energies ͑380 cm −1 ͒, 4 which translate to lower nonradiative transition rates and, thus, higher quantum efficiencies of their optical transitions. Second, the design of a desirable preparation procedure is crucial, as it determines the charge state of the RE ions and local coordination environments around the dopants.…”
Section: Introductionmentioning
confidence: 99%
“…This provides insight into the local coordination environments and the origins of the PL spectral features of these nanostructured samples, from the long-range order down to the local environment of the trivalent erbium cations. 9,11,[24][25][26] Although these types of experiments have been previously conducted on bulk, thin film, and nanoparticle systems of some RE ion doped oxide materials, only a few studies using synchrotronbased analysis of RE-doped NT oxides have been reported. 5,[12][13][14][15]…”
Section: Introductionmentioning
confidence: 99%
“…Such a compound could be yttrium oxide ͑Y 2 O 3 ͒, in fact, both Y 2 O 3 and Er 2 O 3 have the same bodycentered cubic ͑bcc͒ crystalline structure with a lattice parameter mismatch lower than 1%; 9,10 therefore, the Er atoms can be placed in the substitutional sites of Y ions. 11 In particular, both metal ions can occupy two different sixfold coordinated cationic sites, with a C 2 or a C 3i point group symmetry, having a population ratio of 3:1.…”
Section: Introductionmentioning
confidence: 99%